Assessing the educational impact of the dementia champions programme in Scotland: Implications for evaluating professional dementia education. (December 2018) - Jack-Waugh, A.; Ritchie, L.; MacRae, R.
Abstract: Increasing numbers of people with dementia are living longer with a higher likelihood of requiring hospital care for physical conditions including falls, infections and stroke (Boaden, 2016). However, the literature is replete with descriptions of poor care and hospital care experiences that have fallen well below the expectations of people with dementia, their families and friends. Although poor care is unacceptable, it is unsurprising given that dementia education for health and social care professionals is often inadequate and inconsistent. This results in most healthcare staff being ill-equipped and lacking the confidence to work with people living with dementia. The first of Scotland's National Dementia Strategies committed to "improve the response to dementia in general hospital settings including alternatives to admission and better planning for discharge" (Scottish Government, 2010 ). The educational response was the commissioning of the Dementia Champions programme. Since 2011, the programme has developed over 800 health and social care professionals working in general hospital and related settings to be change agents in dementia care. This article will outline the theoretical underpinning of the programme and present pooled results from four cohorts (2014–2017) (n = 524). A repeated measure design (pre and post programme) was used to measure attitudes towards people with dementia; self-efficacy and knowledge of dementia. The findings suggest that the education had a statistically significant positive effect on all intended outcomes, indicating the potential for practice change. We discuss these findings in relation to the literature, and respond to the calls for high quality evaluation to measure the effectiveness of dementia education, the challenges and potential directions for measuring educational effectiveness and capturing transfer of learning.